Legal Protection by the Sexual Violence Prevention and Handling Task Force for Student Victims of Sexual Violence at Andalas University - Iqbal, Tavialsyah; Zurnetti, Aria (Universitas Sultan Ageng Tirtayasa, 2025)
Minister of Education, Culture, Research and Technology Regulation Number 30 of 2021 is a regulation formed by the government and regulates the prevention and handling of sexual violence in higher education. The mandate of this regulation is to prevent sexual violence in the university environment and also strengthen the handling of sexual violence through assistance, victim recovery, administrative sanctions and victim protection. Andalas University in September 2022 established the Sexual Violence Prevention and Handling Task Force (PPKS). From the beginning of the establishment of the PPKS Task Force of Andalas University until now there have been 21 (twenty-one) cases of sexual violence, 20 (twenty) cases only reached the PPKS Task Force level and 1 (one) case has reached the court stage. This study aims to answer questions related to 1) How is the provision of legal protection by the PPKS Task Force for student victims of sexual violence at Andalas University. This research is written with a juridical sociological (empirical) method and sought data directly in the field, which is descriptive in nature using primary and secondary data sources. Data that has been collected, processed and analyzed qualitatively. The results of the study found that the legal protection provided by the PPKS Task Force of Andalas University is preventive and repressive legal protection, preventive legal protection is socialization and education about the prevention and handling of sexual violence in the Andalas University environment, for repressive legal protection including confidentiality of the reporter's identity, protection of physical and non-physical threats, guarantee of continuing education for the reporter, guarantee of continued employment for educators.